KEDUDUKAN LEMBAGA NEGARA ANTARA INDONESIA DENGAN FILIPINA - Nety Hermawati; Desta Lia; Nency Octora (IAIN Metro, 2022)
In a democratic country, it must have a system or constitutional order and there is a separation of powers. This relates to the institutions that exist in a sovereign country, namely the Indonesian state and the Philippines. Bearing in mind that the states of Indonesia and the Philippines are countries based on democratic law, the existence of a representative institution can be an alternative as well as a liaison between the state and its people or community aspirators in order to achieve a sovereign society. The method in this study uses a comparative research method, namely comparing an object with other objects in this case discussing state institutions between Indonesia and the Philippines.